Strategi Pendidikan Berbasis Deep Learning dan Psikologi Peserta Didik: Menuju Pendidikan Berkualitas - Hartoyo; Moch. Ridwan Al Murtaqi (https://journal.metanusantara.com/pedagogia, 2025)
ABSTRACT Quality education is the primary goal of modern learning systems. This study aims to evaluate the effectiveness of educational strategies based on deep learning and student psychology in improving education quality. Using an experimental approach in a quantitative study, this research involved 10th-grade students in a high school in Blora who had been using an adaptive learning platform powered by deep learning for one semester. Data were collected through questionnaires, interviews, and observations, with random sampling techniques ensuring a representative sample. Primary data were obtained from students and educators, while secondary data were gathered from academic documentation and relevant literature. Data analysis was conducted using descriptive and inferential statistical methods, including t-tests and analysis of variance (ANOVA) to test research hypotheses. The findings indicate that implementing deep learning-based educational strategies and student psychology significantly enhances education quality. Deep learning technology enables a more personalized and adaptive learning experience, while a positive psychological approach improves students' motivation and psychological well-being. The validity of the study was ensured through data triangulation, expert validation, and instrument reliability testing. The study concludes that integrating deep learning technology with psychological education approaches offers an innovative solution to enhance learning effectiveness in the digital era.